Strategi Peningkatan Kualitas Pelayanan Perusahaan Otobus NPM - Putri, Suci Rahma; Frinaldi, Aldri (PUBLICNESS: Journal of Public Administration Studies, 2023)
The purpose of this study is to analyze the strategy of improving land transportation. This type of research is qualitative. The results showed that the analysis of aspects for qualitative improvement strategies for services including tangible aspects there are still facilities that need improvement, from the aspect of empathy (empathy) some employees in providing services still do not understand the needs of service users, from the aspect of responsiveness (responsiveness) namely the response to community complaints is still slow and less responsive, from the aspect of reliability (reliability) the services provided are quite accurate but There are still delays, and the last aspect of assurance is that supervision is not optimal and lack of greetings and greetings. Constraints on the NPM Bus Company's Service Quality Improvement Strategy lack of public understanding as service users, Some facilities and infrastructure that need repair and replacement, There are events that cannot be predicted in real time, Sometimes there are delays in departure, Things happen that interfere with the security, comfort, and safety of passengers. Finally, solutions in facing the constraints of the NPM Bus Service Quality Improvement Strategy, solutions include conducting regular performance evaluations to improve service quality, Recruiting employees with strict selection and according to their respective potentials and given training, checking, maintenance, and repairing and improving infrastructure, arranging travel routes with the right calculations and finding alternative ways to avoid obstacles on the way, and providing socialization and education in the form of animated videos or visual orientation to the community.